2005
DOI: 10.1111/j.1467-9280.2005.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

A Warm Heart and a Clear Head

Abstract: Prior studies on the association between weather and psychological changes have produced mixed results. In part, this inconsistency may be because weather's psychological effects are moderated by two important factors: the season and time spent outside. In two correlational studies and an experiment manipulating participants' time outdoors (total N = 605), pleasant weather (higher temperature or barometric pressure) was related to higher mood, better memory, and "broadened" cognitive style during the spring as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 365 publications
(249 citation statements)
references
References 40 publications
11
234
2
2
Order By: Relevance
“…These survey results indicate that people indeed believe that weather will impact their productivity and that bad weather conditions in particular will be detrimental to productivity. This conventional wisdom may be based on the view that bad weather induces a negative mood and therefore yields harmful effects on executive functions (Keller et al 2005). In contrast to this view, we propose that bad weather actually increases productivity through an alternative psychological route.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…These survey results indicate that people indeed believe that weather will impact their productivity and that bad weather conditions in particular will be detrimental to productivity. This conventional wisdom may be based on the view that bad weather induces a negative mood and therefore yields harmful effects on executive functions (Keller et al 2005). In contrast to this view, we propose that bad weather actually increases productivity through an alternative psychological route.…”
Section: Introductionmentioning
confidence: 81%
“…Our data-entry tasks in Study 1 and 2 required workers to pay attention to the given task. Another possibility is that, as Keller et al (2005) noted, positive moods induced by good weather conditions may broaden workers' cognition, thus increasing the flexibility of their thoughts. Consequently, future research should include different types of tasks that require not only attention but also creativity.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of weather on human emotion and social interactions is well supported in the literature. It has been shown that weather has both seasonal and daily effects on mood; it is associated with productivity levels, emotional crises, hostility, memory, and cognition (Denissen, Butalid, Penke, & van Aken, 2008;Persinger, 1975;Barnston, 1986;Dubitsky, Weber, & Rotton, 1993;Keller, et al, 2005).…”
Section: Does Weather Actually Affect Tipping? An Empirical Analysis mentioning
confidence: 99%